STATEGI KOMUNIKASI NINIAK MAMAK PERSUKUAN DALAMPENYELESAIAN SANGKETA HARTA WARISAN DI SUKU PILIANG SONI DESA TANJUNG BONAI KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR - Andri Noviar; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Ulayat land is a community land area with certain costomary law in a regional. The boundaries of an ulayat land are usually determined by valleys, rivers or creecks, certain plants (coconut trees, betel nuts, bamboo clumps etc), hills or hillsides, mortars (traditional rice or grain). This ulayat land is recognized in costumary law. Minangkabau area consists of many nagari. Nagari is a legal community unity that has the boundaries of the territory authorized to regulate and manage the interests of local communities, based on origin and customs that are recognized and respected in a the system of government of the unitary state of the Indonesian Repiblic.West sumatra is famous for its various tribes in the village, this nagari is an autonomous region with the highest power in Minangkabau, no other social and political power can interfere with adat in a nagari. One of which is the piliang soni tribe in the village of Tanjung Tangah, nagari (kelurahan) og Tanjung Bonai, sub-district of Lintau Buo north of flat land district having different Pusako land. Among them is harato pusako high, harato pusako high commonly called in adat tabilang ameh, that is result cancan latiah ancestors inherited by descending line maternal lineage.Key word: communication strategy niniak mamak fellowship in settlement disputes inheritance piliang soni village Tanjung Bonai sub district Lintau Buo north district flat land.